2020
DOI: 10.3390/nu12041071
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Apple Polyphenol Supplements for Skin Conditions in Healthy Women: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: This clinical study was performed to evaluate the effects of continuous apple polyphenol (AP) administration on facial skin conditions and pigmentation induced by ultraviolet (UV) irradiation in healthy women participants. Participants (n = 65, age 20–39 years) were randomized to receive tablets containing AP (300 or 600 mg/day) or placebo in a double-blinded, placebo-controlled clinical trial. Continuous administration of AP for 12 weeks significantly prevented UV irradiation induced skin pigmentation (erythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…5), which indicated increased DNA damage; and continuous DNA lesions compromise the integrity of the genome [35], with genome stability critical for the survival, growth, and normal functioning of organisms [36][37][38]. ROS induce DNA-base damage, and single-and double-stranded breaks (DSBs) [39]; with DSBs constituting the most dangerous type of DNA lesion in cells [40][41][42][43]. To maintain stability, then, the delay or arrest of the cell cycle must occur to allow sufficient time for effective DNA repair [44].…”
Section: Discussionmentioning
confidence: 99%
“…5), which indicated increased DNA damage; and continuous DNA lesions compromise the integrity of the genome [35], with genome stability critical for the survival, growth, and normal functioning of organisms [36][37][38]. ROS induce DNA-base damage, and single-and double-stranded breaks (DSBs) [39]; with DSBs constituting the most dangerous type of DNA lesion in cells [40][41][42][43]. To maintain stability, then, the delay or arrest of the cell cycle must occur to allow sufficient time for effective DNA repair [44].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has also been used for incorporating apple polyphenols into edible films to examine their effect on microbial activity and it was shown that the films inhibited the growth of L. monocytogenes but not S. enterica serotype Hadar [23] [24]. Human studies have shown other beneficial health activities for apple polyphenols, in which they ameliorated hyperglycemia [25] and protected against UV radiation-induced skin pigmentation [26].…”
Section: Related Antimicrobial Studiesmentioning
confidence: 99%
“…5), which indicated increased DNA damage; and continuous DNA lesions compromise the integrity of the genome [27], with genome stability critical for the survival, growth, and normal functioning of organisms [28][29][30]. ROS induce DNA-base damage, and single-and double-stranded breaks (DSBs) [31];…”
Section: Discussionmentioning
confidence: 99%